IMPLEMENTASI ALAT PERAGA FLIPCARD DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN MELALUI PENDEKATAN TARTILA DI TPQ AL-MALIKI PROBOLINGGO - Karomatus Sa’adah; Robiatul Adawiyah; Dinda Ayu Saputri (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
This study aims to improve students’ ability to read the Qur’an through the implementation of flipcard teaching aids using the Tartila approach at TPQ Al-Maliki Mayangan Probolinggo. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 10 students. Data were collected through observation and reading tests, focusing on pronunciation accuracy (makhraj), application of tajwid rules, and reading fluency. The results showed a significant improvement in students’ Qur’an reading ability. In the pre-cycle stage, the learning mastery level was only 30%. After the implementation in Cycle I, it increased to 70%, and in Cycle II, it reached 100%. This improvement indicates that the use of flipcard teaching aids combined with the Tartila approach effectively enhances students’ engagement, understanding, and reading skills. In conclusion, the implementation of flipcard teaching aids through the Tartila approach is effective in improving Qur’an reading ability. This study implies that teachers should utilize interactive and varied instructional media and apply appropriate teaching approaches to create more effective and meaningful learning experiences.